Corporate Social Responsibility sebagai Implementasi Prinsip Tata Kelola Perusahaan Baik pada Asuransi Jiwa Bersama Bumiputra 1912 Cabang Padangsidimpuan - Linni Suraya Lubis (Mahesa Research Center, 2023)
Corporate Social Responsibility (CSR) is a company's social responsibility towards its stakeholders. Good Corporate Governance (GCG) is a framework that regulates the relationships among various parties with interests in a company. One of the principles in Good Corporate Governance is the principle of responsibility, which generates the concept of Corporate Social Responsibility (CSR) as a manifestation of a company's responsibility to society and the environment. This research is a case study titled